Presenting Balanced Geoengineering Information Has Little Effect on Mitigation Engagement - Christine Merk; Gernot Wagner (Center for Economic Studies and ifo Institute (CESifo), 2022)
Moral hazard' links geoengineering to mitigation via the fear that either solar geoengineering (solar radiation management, SRM) or carbon dioxide removal (CDR) might crowd out the desire to cut emissions. We test moral hazard versus its inverse in the first large-scale, revealed-preference experiments (n~340,000) and find that only extreme political messages lead to either outcome for some. Our results indicate the importance of actors and reasoned narratives of geoengineering to help guide public discourse.
Keywords: Q54; Q58; 330; climate change; geoengineering; moral hazard; revealed preference